(untitled) (Revista de Medicina Clinica, 2022)
Introduction: Juvenile nasopharyngeal angiofibroma represents less than 0.05% of head and neck tumors. It originates from the region of the sphenopalatine foramen, can extend into the nasal cavity, paranasal sinuses, pterygopalatine fossa, and the infra-temporal fossa, and may invade base of the skull. The objetive was to evaluate the risk factors associated with the two main surgical techniques for resection of AJNF in a series of cases. Patients and methods: Retrospective, cross-sectional analytical study of a series of cases from 2014 to 2018, demographic variables were taken, as well as clinical and surgical data. Descriptive statistics and analysis were performed with Fisher’s exact test and it was considered significant if p<0.05. Results: Of 24 reviewed files, all were male, the average age 19.3 yr, 41.6% operated endoscopically and 58.3% open surgery. 54.1% had an evolution of symptoms >1 yr and 45.8% <1 yr, stages II and III 91.6% (n = 22) cases, 37.5% (n = 9) with recurrence, a significant difference was found between both techniques (p=0.0333), with greater association with recurrence in the open technique, there was a greater probability of requiring an ICU for open surgeries (p=0.0045), in the same way open surgery has a greater probability of longer stay with p value = 0.0111. No deaths occurred. Conclusion: The endoscopic thecnic seems to be better.